Mobiliário em habitações de caráter social: avaliação de sua adequação espacial em núcleos habitacionais na cidade de Marília - SP - Pires, Mariana Petruccelli [UNESP] (2015)
This study intends to contribute to ongoing discussions on the issue of furniture for social housing can serve as a tool for the adequacy of the minimum space and the furniture. Investigate major conflicts between the built space of social housing and the popular furniture housing units in the city of Marilia, Brazil. It conducted a historical survey of the housing issues of securities of different backgrounds, ages, housing programs and policies, as well as the industrial production issues of popular furniture. To asses the suitability of some furniture for spaces of homes for how-income families, we selected three popular housing units in the city of Marilia, Brazil. He attempted to select cores built by different housing policies at different times and locations. Structured interviews were held with the heads of households selected at random. The results were evaluated separetely for each condominium and few most relevant results were compared between the cores. This study confirmed the hupothesis that there is not adequate in terms of functionality and comfort, furniture for small spaces of affordable housing. The results will serve as a parameter for future design projects as a tool for a better view to addressing this problem